Allylic Oxidations in Natural Product Synthesis - Nakamura, Akihiko; Nakada, Masahisa (Synthesis, 2013)
Although C–H oxidation of hydrocarbons is generally difficult, allylic C–H oxidation is relatively simple and predictable, even on a preparative scale, because active species generated at the allylic position are stabilized by the double bond. Therefore, allylic oxidation has been employed in natural product synthesis, and a variety of reagents and conditions for allylic oxidation have been reported. However, reagents and conditions suitable for natural product synthesis are limited in terms of efficiency and chemo-, regio-, and stereoselectivity, owing to the structural and characteristic diversity of natural products. This review addresses allylic oxidations, highlighting reagents and conditions that meet the requirements for natural product synthesis.1 Introduction2 Selenium Reagents2.1 Selenium Dioxide2.2 Diphenyldiselenide–Iodoxybenzene3 Chromium(VI) Reagents3.1 Chromic Acid and Chromate Ester3.2 Chromium Trioxide–3,5-Dimethylpyrazole (CrO3·3,5-DMP)3.3 PCC and PDC4 Transition-Metal Reagents5 Others6 Conclusion
Keywords: allylic oxidation; C–H oxidation; natural products; selectivity; total synthesis